Avaliação do papel da galectina-3 sobre funções de neutrófilos durante a infecção por cepa virulenta RH de Toxoplasma gondii em camundongos C57BL/6 - Alves, Celene Maria de Oliveira Simões (2009)
Galectins are beta-galactoside-binding animal lectins involved in several biological processes, and Gal-3 has been related to modulation of immune reactions and inflammatory responses. The present study aimed to evaluate the influence of Gal-3 in neutrophil viability, early apoptosis and cell death in parallel with its biological functions after in vivo and in vitro infection with T. gondii RH virulent strain, by using C57BL/6 wild type (Gal-3+/+) and Gal-3 knockout (Gal-3-/-) mice. Gal-3-/- mice exhibit decreased neutrophil recruitment to peritoneal cavity after thioglycolate stimulus, but not after virulent T. gondii RH strain infection, which induced survival curves and morbidity scores similar to Gal-3+/+ mice. Also, higher reactive oxygen species (ROS) generation by inflammatory peritoneal neutrophils was observed in Gal-3+/+ mice infected with this virulent strain and related to early stage of infection. T. gondii infection induced an increase in cell viability and decrease of both phosphatidylserine (PS) exposure and cell death in WT, but not in KO neutrophil. In contrast, parasite infection induced higher LDH release in KO than WT neutrophil. Lysozyme release was higher in KO than WT neutrophil, regardless of infection, but parasite infection induced increased degranulation in WT neutrophil. IL-10 and TNF-α production was modulated by Gal-3, but not by parasite infection. In contrast, higher IL-6 levels were produced by T. gondii infected Gal-3-/- neutrophils. T. gondii infection or STAg stimulation decreased ROS generation induced by PMA in WT neutrophils, but no change was found in KO neutrophils. Zymosan-dependent ROS generation was decreased after T. gondii infection in WT and KO neutrophils. It can be concluded that Gal-3: (1) is essential to increase cell viability by decreasing early apoptosis or cell death in neutrophils induced by T. gondii; (2) decreases neutrophil toxicity caused by parasite infection and diminishes degranulation regardless of infection; (3) modulates pro- and anti-inflammatory cytokine secretion by neutrophils infected or not with T. gondii; (4) is essential for decreased PMA-dependent ROS generation in neutrophils induced by T. gondii infection, but not for decreased zymosan-dependent ROS generation after parasite infection. Therefore, Gal-3 plays an important immunomodulatory role by interfering in neutrophil life span and activation under early infection with virulent T. gondii strain.